Statistical Treatment of Accrual of Intereston Debt Securities - Wright, Chris (IMF Working Papers; Working Paper ;, 2001)
When new international statistical standards were published in 1993, one of the major changes to the recommended presentation of the system of national accounts and the balance of payments was the adoption of accruals reporting for income and expenditure. However, as countries have begun to implement these standards, questions have arisen about their exact interpretation in respect of interest flows associated with tradable debt, where the cash flow is fixed at the time of issue but where the price of the instrument fluctuates with market conditions. A clear consensus has yet to emerge. The paper explores the issues involved in using the alternative approaches, the so-called "debtor" and "creditor" approaches. The debtor approach uses the rate implicit at the time of issue, and the creditor approach, the current market rate. The paper concludes that the creditor approach is the only one consistent with accrual principles and market valuation for the debt outstanding. It reviews implications for national and sectoral saving from this approach.